Multimedia Impact of the Animated Film “Nusa dan Rara” on Speaking and Listening Skills in Early Childhood - Hestu Riza, Moslem Ahmad; Kustiono, Kustiono; Ahmadi, Farid (Journal of Primary Education, 2021)
Speaking skills have a very important role in a child's life. In fact, many children do not have good listening skills so that children have difficulty when talking to other people. This study aims to analyze the multimedia role of the animated film Nusa and Rara in improving speaking and listening skills in children aged 5-6 years. The method in this study used experimental research with a nonequivalent control group design. The population in this study consisted of 200 children aged 5-6 years. The sampling technique used is purposive sampling. The sample in this study were 60 children. Data collection techniques using observation and aneckdotal records. The results showed that the multimedia animation of nusa and rara was effective for improving listening and speaking skills in children after the intervention. The result of the probability hypothesis test is .000 (sig value 0.00 <0.05). This shows that the multimedia animation of nusa and rara is effective in improving listening and speaking skills in children aged 5-6 years at PAUD Mukti Tama